Anionic Cyanine J‐Type Aggregate Nanoparticles with Enhanced Photosensitization for Mitochondria‐Targeting Tumor Phototherapy. Issue 24 (19th April 2022) - Li, Yibin; Ma, Teng; Jiang, Hao; Li, Wei; Tian, Di; Zhu, Jintao; Li, Zhong'an
Abstract: Cyanines have been widely used as the photosensitizers (PSs) in the biomedical field, but controlling their molecular aggregates in nanoparticles (NPs) remains a major challenge. Moreover, the impact of aggregate behaviors of cyanines on the photosensitization is still unclear. Herein, the first anionic cyanine PSs based on a tricyanofuran end group have been designed by achieving supramolecular J‐type aggregates in NPs via counterion engineering. Our results indicate that J‐type aggregates in NPs can not only bring significantly red‐shifted emission, negatively charged surface, and high photostability, but also enable a significant 5‐fold increase in singlet oxygen generation efficiency compared to that in the nonaggregate state, providing strong experimental evidence for the superiority of J‐aggregates in enhancing photosensitization. Thus, combined with the mitochondria‐targeting ability, the J‐type aggregate NPs show remarkable in vivo antitumor phototheranostic efficacy, making them have a potential for clinical use. Abstract : For the first time, anionic cyanines are designed as the phototherapy agents by controlling their aggregates through counterion engineering. The resulting J‐type aggregate nanoparticles show NIR emission, high photostability, negatively charge surface, mitochondria‐targeting ability, and significantly enhanced singlet oxygen generation efficiency, leading to efficient antitumor phototherapy efficacy.